Associations of postnatal growth with asthma and atopy: the PROBIT Study. Issue 2 (3rd February 2013) - Anderson, Emma L.; Fraser, Abigail; Martin, Richard M.; Kramer, Michael S.; Oken, Emily; Patel, Rita; Tilling, Kate
Abstract Background It has been hypothesised that postnatal weight and length/height gain are variously related to wheeze, asthma and atopy; however, supporting evidence is limited and inconsistent. Methods Weights and lengths/heights of 12, 171 term infants were measured from birth to 12 months and at 6.5 yr and extracted from polyclinic records prospectively obtained between 12 and 60 months. Atopic phenotypes were ascertained at 6.5 yr with the International Study of Asthma and Allergy in Childhood questionnaire and skin prick tests. Logistic regression models investigated whether rates of weight and length/height gain from infancy to mid‐childhood were associated with atopy phenotypes that have occurred ever or in the last 12 months. Results After controlling for confounders and prior weight and length/height gain, all weight gain variables except birth weight were positively associated with ever having wheezed (p < 0.1). A one s.d. increase in weight gain rate between 0 and 3 months was associated with a 12% increase (2–23%) in allergic rhinitis ever. No other consistent patterns of association were found for weight gain or length/height gain rate between 0 and 60 months with atopic outcomes at 6.5 yr. In contrast, all atopy outcomes except for ever having asthma were associated with current weight and height, even after controlling for prior growth. Conclusion Current height and weight are more strongly associated with the development of atopic phenotypes in childhood than patterns of infant and early childhood growth, which may well reflect reverse causality (atopy effects on growth) or residual confounding by an unknown common cause of growth and atopy.